Classroom debate as an active methodology for promoting the social and solidarity economy and eco-social transitions at university - Fernández de la Cuadra Liesa, Itsaso; Arcos-Alonso, Asier; Garcia-Azpuru, Amaia (Cooperativismo & Desarrollo, 2025)
This study analyzes the use of classroom debate as a teaching methodology in the course Economic Structure at the University of the Basque Country / Euskal Herriko Unibertsitatea (EHU), within the i³ educational model. The main objective is to assess its potential for developing transversal ethical competences and its coherence with the values of the Social and Solidarity Economy (SSE) and ecosocial transitions. A dual analysis of semi-structured questionnaires applied before and after the experience, together with written productions processed using Iramuteq software, yielded the following results: (1) an improved student perception of their own learning; (2) significant improvements in written expression, information search and autonomous work; (3) greater student motivation, activation and self-confidence; and (4) the perception that classroom debate offers a dialogical, cooperative and ethical space that fosters critical thinking and collective deliberation. The study concludes that classroom debate constitutes a transformative micro-practice that can strengthen the link between academic knowledge, sustainability of life, professional ethics and social commitment, contributing to a transformative higher education oriented towards sustaining life.
Keywords: Social and Solidarity Economy; ecosocial transitions; higher education; active learning; classroom debate